Staying connected: The importance of social integration on the well-being of older adults - STRAUGHAN, Paulin T. (Institutional Knowledge at Singapore Management University, 2020)
It has been about a year since COVID-19 first emerged and reshaped the daily lives of people around the globe, including Singaporeans. Since moving past the circuit breaker in June, Singapore has gradually re-opened and relaxed its restrictions in different phases. As Singapore prepares for Phase 3- the final and least restrictive phase, it is important to examine how Singaporeans have coped and responded with the circuit breaker (7 April 2020) and its gradual easing of restriction in Phase 1 (2nd June 2020) and Phase 2 (19 June 2020), and identify the groups which have fallen through the gaps in Singapore’s recovery. Using data from the Singapore Life Panel (SLP), this research brief outlines the general trends of how older Singaporeans have been coping in the past year- with reference the perceptions towards COVID-19, COVID-19 support grants, employment, social engagements and technology use.